The Development of Indonesian Language Poetry Teaching Materials Based on Suchman's Model to Improve the College Students’ Learning Outcomes - Tussadiah, Halimmah; Febriyana, Mutia; Rahayu, Enny (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research aims to develop the teaching materials for Indonesian language poetry based on the Suchman’s model which have been tested for validity and feasibility to be used as a teaching material.  Additionally, it aims to test whether the use of developed teaching materials can increase the value of the college students’ learning outcomes in Indonesian poetry study.  This research is a developmental research which refers to four stages of development that consist of (1) defining, (2) designing, (3) developing, and (4) disseminating.  To see the increase in the college students’ learning outcomes, Normalized test (N-Gain) is used.  Derived from the test results, it is concluded that the teaching materials for Indonesian language poetry based on the developed Suchman’s model is valid and feasibly to use. The test results through N-Gain proved that 0.78% is in the good category and there is an increase in the college students learning outcomes with an average value of 81.4.